Implementasi Kompetensi Profesional Guru di Sekolah Menengah Kejuruan Negeri 3 Padang - Shofi Maahiroh Arsy; Rifma Rifma; Sufyarma Marsidin; Sulastri Sulastri (Journal of Educational Administration and Leadership, 2022)
Research in the background on the author's observations regarding the Implementation of Teacher Professional Competence at the State Vocational High School 3 Padang in terms of managing learning programs, mastering learning materials, using media and learning resources, evaluating student learning outcomes. The type of this research is descriptive quantitative. The total population is 1,048 students, with a total sample of 92 students. Calculating the sample size using the Slovin formula with an error of 10% through the Stratified Proportional Random Sampling technique. The questionnaire was used as a research instrument using a Likert scale model which has 5 alternative answers. The results of the data analysis of the implementation of the professional competence of teachers at the State Vocational High School 3 Padang showed that (1) developing learning materials got an average of 3.60 in the good category; (2) mastering learning materials get an average of 3.56 in the good category; (3) using media and learning resources get an average of 3.69 in the good category; (4) carry out evaluation of student learning outcomes to get an average of 3.81 already in the good category.